Una mirada a la representación poética desde la playa de Bacuranao - Ariel González-Rodríguez (Grafía, 2018)
This essay reflects on an existing issue from the very first moment that literature appears in human culture: the problem of poetic representation that makes use of subjective experience and a language that is by all means insufficient and at the same time fascinating, to confront the world, what is understood by the real, or the depths of the self. Rather than attempting to answer a few questions, we want to highlight how the Cuban poet Luis Rogelio Nogueras manages to condense this concern into a brief poem.